2022
DOI: 10.1111/tpj.15889
|View full text |Cite
|
Sign up to set email alerts
|

Spruce giga‐genomes: structurally similar yet distinctive with differentially expanding gene families and rapidly evolving genes

Abstract: SUMMARY Spruces (Picea spp.) are coniferous trees widespread in boreal and mountainous forests of the northern hemisphere, with large economic significance and enormous contributions to global carbon sequestration. Spruces harbor very large genomes with high repetitiveness, hampering their comparative analysis. Here, we present and compare the genomes of four different North American spruces: the genome assemblies for Engelmann spruce (Picea engelmannii) and Sitka spruce (Picea sitchensis) together with improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 114 publications
(162 reference statements)
0
26
1
Order By: Relevance
“…The Sitka spruce ( Picea sitchensis ) is a large, evergreen, and long-living conifer species native to the Pacific Northwest in North America. Although a 20 Gbp draft genome assembly is publicly available 26 , its scaffold N50 length is 56.8 kbp, which reflects the draft stage of this short-read genome assembly. In particular, the Sitka spruce’s alternative splicing pattern has not been fully investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The Sitka spruce ( Picea sitchensis ) is a large, evergreen, and long-living conifer species native to the Pacific Northwest in North America. Although a 20 Gbp draft genome assembly is publicly available 26 , its scaffold N50 length is 56.8 kbp, which reflects the draft stage of this short-read genome assembly. In particular, the Sitka spruce’s alternative splicing pattern has not been fully investigated.…”
Section: Resultsmentioning
confidence: 99%
“…2012), which may suggest lower rates of gene diversification. On the other hand, conifers have suites of rapidly evolving genes (Gagalova et al 2022) and highly diversified gene families or sub-families (e.g., Bedon et al 2010; Stival Sena et al 2018; Van Ghelder et al 2019) both related to stimuli and stress response. Several comparative studies in conifers have shown high levels of intergeneric macro-synteny and macro-collinearity among Pinaceae taxa (Pavy et al 2012) (Pelgas et al 2006; Ritland et al 2011; Westbrook et al 2015) and clear chromosomal rearrangements when comparing Pinaceae and Cupressaceae (Moriguchi et al 2012, de Miguel et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 2019), we tested whether this is a Pinaceae family-wide phenomenon by examining publicly available genomic resources in other members of the family. To characterise the distribution of NLR genes in the speciose Picea genus, we deployed a high-density linkage map for P. abies (Bernhardsson et al 2019) and high-quality genome assemblies of P. glauca and P. sitchensis (Gagalova et al 2022). Although these assemblies do not have chromosome-level contiguity, they are suitably scaffolded into linkage groups corresponding to an updated version of the original P. glauca high-density linkage map (Pavy et al 2017).…”
Section: Genomic Distribution Of Nlr Genes In Pinaceae and Other Coni...mentioning
confidence: 99%
See 1 more Smart Citation
“…These SNPs showed good quality and minor allele frequency (MAF) of at least 6% in previous white spruce studies (Pavy et al, 2017). All selected SNPs were located in coding regions that have a higher probability of sequence conservation and were mapped to the reference maps of Pavy et al (2017) and Gagalova et al (2022). The sequences surrounding the SNPs (at least 75 bp) were blasted against the transcriptome of white spruce (Birol et al, 2013) and only sequences of SNPs with a full hit in the genome were retained.…”
Section: Methodsmentioning
confidence: 99%